The Role of Political Parties as Democratic Infrastructure: A Perspective of Rule of Law - Abhiseka, I Gede Druvananda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
preamble of the 1945 Constitution is a very important declaration in the formation of the Indonesian state. This preamble is not only the opening of all articles in the 1945 Constitution, but also reflects the ideals and goals of the Indonesian nation. It contains the basic principles that form the basis of the state, such as independence, unity and social justice. The link between Article 1(2) and (3) of the 1945 Constitution lies in the strengthening of the principle of democracy within the framework of the rule of law. In this case, popular sovereignty (paragraph 2) is not only articulated in the form of elections or political decision-making alone, but must also be implemented within a fair and binding legal framework as stated in (paragraph 3), and political parties play a very important role as infrastructure in a democratic system. As institutions that unite people's aspirations, political parties have a major function in facilitating citizens' political participation. Political parties act as a bridge between the people and the government, by absorbing, organizing, and conveying the interests of the community into public policy.